Effects of riparian land use changes on soil attributes and concentrations of potentially toxic elements - CUNHA,GIULLIANA KARINE G. (2021)
Abstract Riparian zones are intrinsically sensitive habitats to anthropogenic disturbances. Knowledge about how riparian soil attributes respond to anthropogenic changes remains limited. This information would allow the prediction of degradation and contamination soil scenarios that threaten water quality for supply. Here, we studied the impact on soil quality and concentration that potentially toxic elements caused through changes in land use in riparian soils in northeastern Brazil. A total of thirty riparian soil composite samples were collected from areas with different land use and evaluated for physical and chemical attributes, in addition to potentially toxic elements (Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn). The results showed that replacing the natural vegetation in the riparian zone led to degradation gradient: pasture < agricultural < urban < industrial use. Soil attributes were sensitive in distinguishing the degree of degradation of each land use. Concentrations of the potentially toxic elements Cd and Zn are above the background soil concentrations and may pose a risk to the environment and human health. Our data can be helpful to understand better the complex relationship between land use and environmental impacts in riparian zones in northeastern Brazil and similar settings worldwide.